PENGUKURAN KUALITAS LAYANAN DAN KEPUASAN PELANGGAN PADA HOTEL MESRA AND BUSSINESS RESORT SAMARINDA DENGAN MENGGUNAKAN METODE SERVQUAL DAN IMPORTANT PERFORMANCE ANALYSIS - I Wayan Lanang; Evi Setiyowati (Politeknik Negeri Samarinda, 2016)
The research aims to measure the quality of service provided by Hotel Mesra and Bussiness Resort Samarinda based on the service product dimension (Tangibility, Reliability, Resposiveness, Assurance, and Empathy) and analyzed using the ServQual and Importance-Performance Analysis. The research found the level of customer satifaction index was 78,80% which generaly means that the customers perceived that the service provided able to meet the customers satifactions. The research also found that there are some priorities for improvement due to service gap on dimension of assurance. Kata Kunci : Service quality, Customer satifaction, ServQual, Importance, Performance Analysis.